Сезонные миграции пашенной полевки (Microtus agrestis L.) на субальпийских лугах Черногоры Украинских Карпат. Сообщение I - Пилявский, Б.Р. (Вестник зоологии, 1969)
Data on season migrations of Microtus agrestis L. under the conditions of the Ukrainian Carpathians are given in the article. From 177 marked Microtus argentis L.— 104 were caught for the second time (76— in the same places, 28—in new ones). 83,0% of Microtus agrestis L. remained in the places of catching after the markation during 1—7 days, the others were met during 8—385 days. Microstus agrestis L. dwelling in July-August in Nardetum, at the close of summer they migrate to fir-wood, Deschampsietum, Rumicetum, Myrtilletum, which is conditioned by worsening of the fodder qualities of Nardus stricta and fall of temperature. At the close of May and at the beginning of June, when the green mass of Nardus stricta grows, they return to the polonines to Nardetum.